Enhanced protopanaxadiol production from xylose by engineered Yarrowia lipolytica - Wu, Yufen (Microb Cell Fact, 2019)
BACKGROUND: As renewable biomass, lignocellulose remains one of the major choices for most countries in tackling global energy shortage and environment pollution. Efficient utilization of xylose, an important monosaccharide in lignocellulose, is essential for the production of high-value compounds, such as ethanol, lipids, and isoprenoids. Protopanaxadiol (PPD), a kind of isoprenoids, has important medical values and great market potential. RESULTS: The engineered protopanaxadiol-producing Yarrowia lipolytica strain, which can use xylose as the sole carbon source, was constructed by introducing xylose reductase (XR) and xylitol dehydrogenase (XDH) from Scheffersomyces stipitis, overexpressing endogenous xylulose kinase (ylXKS) and heterologous PPD synthetic modules, and then 18.18 mg/L of PPD was obtained. Metabolic engineering strategies such as regulating cofactor balance, enhancing precursor flux, and improving xylose metabolism rate via XR (K270R/N272D) mutation, the overexpression of tHMG1/ERG9/ERG20 and transaldolase (TAL)/transketolase (TKL)/xylose transporter (TX), were implemented to enhance PPD production. The final Y14 strain exhibited the greatest PPD titer from xylose by fed-batch fermentation in a 5-L fermenter, reaching 300.63 mg/L [yield, 2.505 mg/g (sugar); productivity, 2.505 mg/L/h], which was significantly higher than the titer of glucose fermentation [titer, 167.17 mg/L; yield, 1.194 mg/g (sugar); productivity, 1.548 mg/L/h]. CONCLUSION: The results showed that xylose was more suitable for PPD synthesis than glucose due to the enhanced carbon flux towards acetyl-CoA, the precursor for PPD biosynthetic pathway. This is the first report to produce PPD in Y. lipolytica with xylose as the sole carbon source, which developed a promising strategy for the efficient production of high-value triterpenoid compounds. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-019-1136-7) contains supplementary material, which is available to authorized users.